2013
DOI: 10.1016/j.cep.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion in fully developed flow through regular porous structures: Experiments with wire-mesh sensors

Abstract: Within this study the wire-mesh sensor is proposed as a suitable device to investigate radial and axial dispersion in tubular reactors. Axial dispersion in turbulent flow through a regular highly porous structure is addressed and the effect of reactor length on the estimated axial dispersion coefficient is discussed. We state that the gradual increase of turbulence intensity in the entrance section of the porous structure is an effect which leads to a length dependence of the dispersion coefficient. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…For example, Boskovic and Loebbecke [33] proposed an empirical model for laminar flow regime in micromixers and the task of deconvolution is reduced to time-domain fitting to find the best parameter that matches predicted to experimental results. Similarly, Hafeli et al [37] performed time domain fitting to find the E-function for flow through porous structures by using the well-known axial dispersion model as representative of the flow. Essadki et al [34] solved the deconvolution problem in the frequency domain, and after converting the E-function to the time domain, it was fitted to known reactor models to find the axial dispersion coefficient or the Péclet number.…”
Section: Deconvolution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Boskovic and Loebbecke [33] proposed an empirical model for laminar flow regime in micromixers and the task of deconvolution is reduced to time-domain fitting to find the best parameter that matches predicted to experimental results. Similarly, Hafeli et al [37] performed time domain fitting to find the E-function for flow through porous structures by using the well-known axial dispersion model as representative of the flow. Essadki et al [34] solved the deconvolution problem in the frequency domain, and after converting the E-function to the time domain, it was fitted to known reactor models to find the axial dispersion coefficient or the Péclet number.…”
Section: Deconvolution Methodsmentioning
confidence: 99%
“…Several authors studied the numerical solution of the deconvolution integral [26][27][28][29][30][31][32][33][34][35][36][37][38] and several techniques are available in the [26], their method requires a smoothing filter in the frequency and time domains. Nahman and Guillaume [28] studied both frequency and time domain methods for the deconvolution and concluded that the frequency domain method implemented via FFT is by far superior to the time domain methods.…”
Section: Deconvolution Methodsmentioning
confidence: 99%
“…However, limitations exist for application in micro-devices diagnosis: the intrusive character of the method, the size of the probes and their response time (generally a few seconds). However new devices are proposed in response to these limitations such as wire-mesh sensors (Elias and Rudolf von Rohr, 2016;Häfeli et al, 2013). -Optical detection: although the material is expensive and fragile, optical detection (e.g.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Alternatively, it is possible to devise portable CT systems that can achieve relatively high spatial resolution and full tomographic reconstructions, though these may have other restrictions regarding the size of the equipment on which they can be applied (Bieberle et al, 2013;Kim et al, 2012). Electrical tomography techniques have also proven beneficial for studying trickle bed reactors owing to the high time resolution that can be achieved (Bieberle et al, 2010;H€ afeli, Hutter, Damsohn, Prasser, & Rudolf von Rohr, 2013;Llamas et al, 2008;Matusiak, Jose, Hampel, & Romanowski, 2010;Reinecke & Mewes, 1997). Measurements of the conductivity require the conductive phase to be continuous, which is not often the case in a trickle bed.…”
Section: Hydrodynamic Studiesmentioning
confidence: 97%